Household expenditures, wages, rents - Morris A. Davis; François Ortalo-Magné (Center for Economic Studies and ifo Institute (CESifo), 2007)
We provide new evidence from the 1980, 1990, and 2000 Decennial Census of Housing that the expenditure share on housing is constant over time and across U.S. metropolitan areas (MSA). Consistent with this observation, we consider a basic model in which identical households with Cobb-Douglas preferences for housing and numeraire consumption choose an MSA in which to live and MSAs differ with respect to income earned by residents. We compute constant-quality wages and rental prices for a sample of 50 U.S. MSAs. Given estimated wages, the calibrated model predicts that rental prices should be more dispersed than observed. That is, the model suggests that rental prices are too low in many high-wage MSAs in the year 2000.
Keywords: D10; R21; 330; household expenditures; housing prices; Cobb-Douglas utility; Verbraucherausgaben; Grundbesitz; Ballungsraum; Immobilienpreis; Mikroökonomische Konsumfunktion; USA